An outbreak of diarrhoeal disease of El Tor Vibrio cholerae O1 Ogawa in and around Yavatmal district, Maharashtra, India in 2018 - Kale, Swati S.; Bulle, Pragati A.; Deshmukh, Durgesh G.; Tankhiwale, Supriya S.; Gujar, Vivek M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Epidemics of cholera have been reported from various parts of India. We investigated the epidemic of cholera that occurred in and around Yavatmal district in Maharashtra, India 2018, reported during March to July. Methods: 711 stool samples collected from diarrhea patients were bacteriologically analyzed for their identification and antibiogram of Vibrio cholera. Results: The cholera outbreak was caused by V. cholerae O1 Ogawa biotype El Tor. All the V. cholerae isolates from the stool samples were sensitive to tetracycline, doxycycline, ofloxacin, ciprofloxacin gentamycin, cotrimoxazole and resistant to ampicillin and ceftazidime. Conclusions: The present outbreak was due to V. cholerae O1 Ogawa El Tor which seems to have completely replaced O139 serogroup of the previous outbreaks during the last decade.